Effects of vitamin D supplementation on insulin sensitivity and androgen levels in vitamin-D-deficient polycystic ovary syndrome patients - YOLDEMİR, AHMET TEVFİK; YAVUZ, DİLEK (WILEY, 2018)
AimThe aim of this study was to identify the effects of vitamin D supplementation on insulin sensitivity and androgen levels in vitamin-D-deficient polycystic ovary syndrome (PCOS) patients. MethodsSixty-seven vitamin-D-deficient (25-hydroxyvitamin D [25(OH)D] levels below 20ng/mL) PCOS patients and 54 vitamin-D-deficient non-PCOS volunteer subjects matched for age and body mass index were enrolled to this prospective study. All participants were given 50000IU/week cholecalciferol orally for 8weeks and 1500IU/day for 4weeks. Insulin sensitivity was calculated with the Matsuda insulin sensitivity index (ISI) based on an oral glucose tolerance test. Matsuda ISI, gonadal hormones (estrogen, testosterone, androstenedione), and 25(OH)D levels were studied before and at the end of the 12th week of vitamin D load. ResultsAfter vitamin D supplementation, serum androstenedione levels had decreased significantly (P=0.007) and Matsuda ISI values had increased significantly (P=0.001) in the PCOS group but no significant changes were seen in those parameters in controls. We observed positive correlations between 25(OH)D levels and Matsuda ISI (r=0.307; P< 0.01), and negative correlations between 25(OH)D levels and total testosterone (r=-0.306; P< 0.01) and androstenedione (r=-0.275; P< 0.01) levels in the PCOS group. ConclusionVitamin D supplementation increased insulin sensitivity and decreased androgen levels in vitamin-D-deficient women with PCOS but did not have any effect in vitamin-D-deficient non-PCOS women. These results may indicate the possible role of vitamin D in the complex pathogenesis of PCOS.
Keywords: insulin sensitivity; Matsuda insulin sensitivity index; polycystic ovary syndrome; total testosterone; vitamin D; METABOLIC DISTURBANCES; GLUCOSE-METABOLISM; HYPOVITAMINOSIS-D; SYNDROME WOMEN; RISK-FACTORS; RESISTANCE; TOLERANCE